TRAINING ON THE PRESENTATION OF MOSQUE FINANCIAL STATEMENTS FOR INCREASED SUSTAINABILITY, TRANSPARENCY AND ACCOUNTABILITY AT THE MOSQUE AT TADZIKRO SIDOARJO - Wany, Eva; Prayitno, Budi; Yustie, Renta (Antis-publisher, 2026)
Objective: The objective of this study is to emphasize the importance of accurate and precise financial reporting in non-profit organizations, particularly in mosques, to ensure accountability and transparency to donors. Method: This research discusses the financial management practices of mosques, with a focus on voluntary donations from the public and the reporting requirements for managing and accounting for these funds. It highlights the role of good financial information systems in aiding decision-making for mosque administrators. Results: The study finds that effective financial management reflects the trustworthiness and responsibility of mosque administrators in managing donations, contributing to accountability and transparency. Novelty: The novelty lies in linking accountability with the specific financial management needs of mosques, emphasizing the importance of transparency in managing voluntary donations for public trust and organizational performance.